Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.pupt.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuraminidase on equine isolated bronchi

Abstract: A c c e p t e d m a n u s c r i p t AbstractIt has been demonstrated in mammals that the airway hyperresponsiveness which accompanies viral infections is the result of increased reflex bronchoconstriction due to inhibition of muscarinic prejunctional receptors, which belong to M2 subtypes. Multiple mechanisms account for virus-induced M2 receptor dysfunction. Viral neuraminidase may deglycosylate the M2 receptor, decreasing acetylcholine affinity. Equine influenza remains a common viral respiratory disease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Although the response of isolated human ASM may not always be identical to that elicited in vivo, isolated airway preparations provide a suitable, convenient, and reproducible biological model for the evaluation of drug effects on ASM independent from the potential systemic influences found in vivo (Endoh and Hori, 2006;Iglarz et al, 2008). In particular, the configuration of the smooth muscle bundles is largely preserved in human isolated bronchi and therefore the bronchial contraction is directly related to airway narrowing Cazzola et al, 2011Cazzola et al, , 2012Hewson et al, 2012;Hulsmann and de Jongste, 1993;Matera et al, 2005Matera et al, , 2008Matera et al, , 2009Matera et al, , 2011aMatera et al, , 2011bRogliani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the response of isolated human ASM may not always be identical to that elicited in vivo, isolated airway preparations provide a suitable, convenient, and reproducible biological model for the evaluation of drug effects on ASM independent from the potential systemic influences found in vivo (Endoh and Hori, 2006;Iglarz et al, 2008). In particular, the configuration of the smooth muscle bundles is largely preserved in human isolated bronchi and therefore the bronchial contraction is directly related to airway narrowing Cazzola et al, 2011Cazzola et al, , 2012Hewson et al, 2012;Hulsmann and de Jongste, 1993;Matera et al, 2005Matera et al, , 2008Matera et al, , 2009Matera et al, , 2011aMatera et al, , 2011bRogliani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, since bronchial desensitization may be mediated by the activation of nonmyelinated C‐fibers and release of non‐neurogenic acetylcholine, the impact of a combination of tiotropium bromide and olodaterol on the contractile response elicited by EFS 3 Hz suggests that ultra‐LABA/LAMA combinations may have a role in preserving the physiological bronchial tone necessary to protect equine airways from the insult of external airborne agents. In this regard, severe asthmatic horses may benefit from preventive treatment with dual bronchodilation therapy that may support the pulmonary function in those horses that are at risk of bronchoconstriction, such as those having a viral influenza infection or undergoing sedation (Calzetta, Soggiu, et al., ; Matera et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Vagal firing largely determines the equine bronchial tone (Matera et al, 2002), and transmural stimulation of isolated airways activates vagal postganglionic fibers (Matera et al, 2008;Olszewski et al, 1999). Several neurotransmitters are released by transmural stimulation, the most representative is acetylcholine released by myelinated fibers, whereas nonmyelinated fibers mainly sustain neurogenic airway inflammation (Belvisi, 2002;Calzetta, Luongo, et al, 2015;Yu, Wang, & Robinson, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the response of human isolated ASM strictly resembles that elicited in vivo Cazzola et al, 2011Cazzola et al, , 2012Matera et al, 2009Matera et al, , 2011aMatera et al, ,b 2005Matera et al, , 2008Rogliani et al, 2013), results obtained from ex vivo studies need to be confirmed in clinical trials.…”
Section: Introductionmentioning
confidence: 99%